The effectiveness of principal’s competencies implementation at SMAN 3 and Internasional Budi Mulia Dua Yogyakarta - Vikate Phannalath; Lantip Diat Prasojo (Jurnal Akuntabilitas Manajemen Pendidikan, 2017)
This study aimed to evaluate the effectiveness of principal’s competencies implementation at SMA Negeri 3 Yogyakarta and SMA Internasional Budi Mulia Dua Yogyakarta, Indonesia. The research was an evaluation research using the discrepancy model of evaluation. The respondents were vice principals, teachers, as well as administrative officers. The data was collected through the questionnaires, the results of the study showed that the effectiveness of the principal’s competencies implementation at SMA Negeri 3 Yogyakarta is: personality competencies 78.84% effective, managerial competencies 82.69% effective, entrepreneurship competencies 78.84% effective, supervision competencies 84.61% effective, and social competencies 86.53% effective, while in the SMA Internasional Budi Mulia Dua was:  personality competencies 100% effective, managerial competencies 100% effective, entrepreneurship competencies 100% effective, supervision competencies 96% effective, and social competencies 100% effective. The effectiveness of the principal’s competencies implementation of SMA Internasional Budi Mulia Dua Yogyakarta was better compared to SMA Negeri 3 Yogyakarta.Keywords: the effectiveness of personality competencies, managerial competencies, entrepreneurship competencies, supervision competencies, social competencies